FAKTOR-FAKTOR YANG MENGHAMBAT PENANDATANGANAN INDONESIA JAPAN ECONOMIC PARTNERSHIP AGREEMENT (Studi Komparasi Indonesia dan Negara-negara ASEAN) - , ASTRID RAMADIAH WIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to determine the delay of Indonesia in cooperation signing economic partnership with Japan, or better known as the EconomicPartnership Agreement (EPA). This delay benchmarks when compared withcountries in Southeast Asia, like Singapore, Malaysia, Thailand, Philippines, andBrunei Darussalam. Japan Economic Partnership is a form of efforts to improve free trade andinvestment cooperation. Bids economic partnership with Japan's cooperation tocooperation partner countries in Southeast Asia alone has rolled from 2000, but the Indonesian Government response to efforts to follow up such cooperation tends to be slow when compared to its neighboring countries of Southeast Asia region. The delaywill then affect the credibility of Indonesia as a founding member of ASEAN and has astrategic role for Japan. Delays in Indonesia is due to the factors that tendency comes from Indonesia's owninternal state, whether the problem Infrastructure, Human Resources, as well asperformance ditataran Indonesia inefficient bureaucracy. Given this research it isexpected that the Indonesian Government could make improvements to the factorsthat weaken the position of Indonesia's competitiveness in Southeast Asia and International.